Fiscal rules and regime-dependent fiscal reaction functions The South African case - Burger, Philippe (OECD Publishing, 2012)
This article argues the case for a policy of "anchored flexibility" in the form of a flexible fiscal rule that allows for the pursuit of economic stability but always anchors that pursuit in fiscal sustainability. The rule is explicitly structured to be simple and is designed in analogy to the inflation-targeting framework. The article heeds the warning that consistently forecasting the output gap with any degree of precision is quite difficult, if not impossible, and thus proposes a target band for the deficit, instead of point targets for the overall deficit and the structural budget balance. To ensure fiscal sustainability over and above the contribution of the deficit rule, the article also proposes a band for the debt/GDP ratio. This debt rule acts as a negative feedback rule that stipulates the adjustments required in the deficit, should the actual debt/GDP ratio move outside the stipulated band. Since the government needs to change revenue and expenditure in order to change the deficit, the article then explores empirically whether and with how much revenue and expenditure in South Africa changed to maintain fiscal sustainability. More specifically the article explores various models of the fiscal reaction function to illuminate government behaviour in South Africa. These models consider how the deficit, expenditure and different types of revenue reacted to the debt/GDP ratio and the output gap to ensure fiscal sustainability. Lastly, the article considers measures that could enhance the automatic stabilisers, while simultaneously allowing for the maintenance of fiscal sustainability in the medium term